Work Related Health Problems and Healthcare Seeking Among Tea Garden Worker (Journal of Preventive and Social Medicine, 2025)
Background: Tea, derived from the Camellia sinensis plant, is a globally consumed beverage with a rich history. Despite its widespread production, smaller gardens produce unique teas highly valued by enthusiasts. The tea industry in Bangladesh, particularly in Sylhet, plays a pivotal role in the economy but is plagued by challenges such as work-related health issues among its predominantly marginalized and tribal labor force. This study aimed to explore the health and lifestyle challenges faced by tea workers in Sylhet. Methods: A cross-sectional study was conducted in three tea gardens in Sylhet, focusing on socio-demographic characteristics, work-related health problems, and healthcare-seeking behaviors. Data were collected from 255 participants using a semi-structured questionnaire, and statistical analyses, including Chi-Square test, were performed using SPSS version 26. Results: The socio-economic profile revealed a predominantly female, Hindu, and illiterate workforce with low income. Musculoskeletal disorders (MSDs) were prevalent, affecting 77.6% of participants, with lower back pain being the most common. Common diseases, injuries, and respiratory issues were reported. Allopathic treatment was preferred by 78% of respondents. Significant associations were found between MSDs and age, education, smoking, and drug use. Job-related factors like nature of work and weekly working hours also showed significant associations (p